Does the Mass Balance of the Reactive Tracers Resazurin and Resorufin Close at the Microbial Scale?. Issue 2 (20th February 2020) - Dallan, Eleonora; Regier, Peter; Marion, Andrea; González‐Pinzón, Ricardo
Abstract: Resazurin (Raz) is a phenoxazine dye that can be reduced irreversibly to the daughter compound resorufin (Rru) by aerobic respiration. Previous hydrologic studies using the Raz‐Rru reactive tracer system to quantify water‐sediment interactions and metabolic activity have reported that dilution‐corrected masses of Raz and Rru recovered are smaller than the mass of Raz injected. This lack of mass balance closure has been reported as a nonideality of this tracer system and, to date, it is still unclear what drives incomplete recovery. We used controlled laboratory experiments varying the initial concentrations of Raz, the duration of the experiments, and the type of microbial communities present to quantify mass balances of Raz and Rru under conditions that removed other suspected causes of incomplete recovery in field experiments, i.e., sorption to sediments and photodecay. We used the summation of Raz and Rru concentrations over time to assess mass recovery and variability and found mass recoveries in the range of 85.6–110.4%, with a maximum standard deviation of 7.5%. In three of the four experiments, no strong temporal trend in mass recovery is present. In an experiment with Bacillus subtilis bacteria, lower recovery and evidence of a temporal trend in recovery only occurred after 13 hr past the complete transformation of Raz (i.e., beyond the duration of most field experiments). These results suggest that the lack of mass recovery in field studies is likely associated with physical or chemical mechanisms rather than biological interactions with the Raz‐Rru tracer system. Plain Language Summary: Resazurin (Raz) is a fluorescent dye that can be transformed into resorufin (Rru) by microorganisms. It has been used for a decade to study how water interacts with sediments and microbial communities. However, most of these studies recover less Raz and Rru than the Raz that was added, prompting the question: Does the mass balance of Raz and Rru close at the microbial scale? We conducted multiple experiments with different microbes to answer this question. Our results generally show full mass recovery, meaning that the incomplete recovery reported in field studies is governed by physical or chemical factors. Key Points: Mass balances were used to assess if microbial transformation explains incomplete recovery of resazurin‐resorufin in field studies Experiments conducted with different microorganisms indicate complete mass recovery during all conversion stages Complete mass recovery at the microbial scale suggests sorption is responsible for incomplete recovery in mesocosm and field experiments